Cerebrospinal fluid neurofilament light chain predicts short-term prognosis in pediatric Guillain-Barré syndrome - Jin, Mei; Liu, Kang; Zhao, Libo; Liu, Jing; Zhao, Ziwei; Zhao, Yifan; Sun, Suzhen (Frontiers in Neurology, 2022)
Introduction: To study cerebrospinal fluid neurofilament light chain (CSF-NfL) levels as a prognostic biomarker in pediatric Guillain-Barré syndrome (GBS). Methods: Prospective study enrolling 26 pediatric GBS patients and 48 healthy controls (HCs) from neurology units between 2017 to 2021. The CSF-NfL levels were measured by enzyme-linked immunosorbent assay. The children’s disability levels were evaluated using Hughes Functional Score (HFS) at nadir, 1 month, and 6 months after onset. Receiver operating characteristic (ROC) curve derived from logistic regression (with age as a covariate) was used to assess the prognostic value of CSF-NfL on the possibility of walking aided at 1 month after symptom onset. Results: The mean CSF-NfL levels were significantly increased in GBS patients (111.76 pg/mL) as compared to that in HCs (76.82 pg/mL) (t =6.754 , p＜0.001).At follow- up, the mean CSF-NfL levels after treatment (65.69 pg/mL ) declined significantly (t=6.693, p ＜0.001). CSF-NfL levels upon admission were significantly associated with the HFS at nadir (rs = 0.461, p = 0.018). Moreover, the mean CSF-NfL levels in GBS patients with poor prognosis(130.47pg/mL) were significantly higher than that in patients with good prognosis(104.87pg/mL) (t=2.399，p=0.025). ROC curve analysis of the predictive value of CSF-NfL levels with respect to inability to walk unaided within 1 month showed a significant difference (area under the curve: 0.857,95% confidence interval 0.702-1.000; p = 0.006). Conclusion: CSF-NfL levels were increased in pediatric GBS patients. High CSF-NfL level predicted worse motor function, and was strongly associated with poor short-term prognosis of pediatric GBS. We propose a biomarker for early prediction of outcome in pediatric GBS, which would be applicable for clinical practice and efficacy of treatment in the future.